2014
DOI: 10.1051/0004-6361/201424047
|View full text |Cite
|
Sign up to set email alerts
|

Characterising superclusters with the galaxy cluster distribution

Abstract: Superclusters are the largest observed matter density structures in the Universe. Recently, we presented the first supercluster catalogue constructed with a well-defined selection function based on the X-ray flux-limited cluster survey, REFLEX II. To construct the sample we proposed a concept to find large objects with a minimum overdensity such that it can be expected that most of their mass will collapse in the future. The main goal is to provide support for our concept here by using simulation that we can, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
31
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 38 publications
9
31
0
Order By: Relevance
“…The mass-to-light ratios of the SGW superclusters, M/L ≈ 300 h M /L , are close to the values of the mass-to-light ratios for other rich superclusters (Gavazzi et al 2004;Schirmer et al 2011;Einasto et al 2015). Moreover, the components in rich SGW superclusters have masses that are comparable to the masses of simulated superclusters of average richness (Chon et al 2014;Araya-Melo et al 2009). The masses of rich SGW superclusters are of the same order as the high end of simulated supercluster masses.…”
Section: Discussion and Summarysupporting
confidence: 71%
See 1 more Smart Citation
“…The mass-to-light ratios of the SGW superclusters, M/L ≈ 300 h M /L , are close to the values of the mass-to-light ratios for other rich superclusters (Gavazzi et al 2004;Schirmer et al 2011;Einasto et al 2015). Moreover, the components in rich SGW superclusters have masses that are comparable to the masses of simulated superclusters of average richness (Chon et al 2014;Araya-Melo et al 2009). The masses of rich SGW superclusters are of the same order as the high end of simulated supercluster masses.…”
Section: Discussion and Summarysupporting
confidence: 71%
“…The main uncertainty of supercluster masses comes from missing groups and clusters, and from the mass estimate of faint groups. The bias between the masses of superclusters determined using group masses and the total mass of the supercluster have been studied from simulations (Chon et al 2014). They showed that the bias between masses depends on the richness of groups; it is lower when low-mass groups are used to construct the supercluster catalogues.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…For the details of the construction of the superclusters in simulations, we refer the readers to Chon et al (2014). The value of r Δ was taken at the radius where the density ratio reaches the threshold value for collapse, and r v is defined as the radius where the required infall velocity is reached.…”
Section: Comparison Of Overdensity and Dynamical Criteriamentioning
confidence: 99%
“…To evaluate the total mass of Shapley with the REFLEX II clusters, we also considered the total cluster mass as a function of a radius for the same volume. We converted the total cluster mass to the total supercluster mass by adopting a scaling relation found with cosmological N-body simulations in Chon et al (2014). We find that the required density ratio for collapse is satisfied out to about 12.4 h −1 Mpc.…”
Section: Shapley Superclustermentioning
confidence: 99%
See 1 more Smart Citation